Association of C-reactive protein positivity among groups of patients with knee osteoarthritis in Erbil - Pirdawood, Helen Ahmed; Jawad, Niaz k. (Zanco Journal of Medical Sciences (ZJMS), 2017)
Background and objective: Osteoarthritis is the most common joint disease and a leading cause of disability. Increased circulating levels of C-reactive protein have been associated with prevalent knee osteoarthritis. This study aimed to assess the association between C- reactive protein positivity in patients with knee osteoarthritis in Erbil Methods: Data from100 participants in this case-control study were enrolled from May 1st to December 1st, 2015 in Rizgary Teaching Hospital in Erbil city. Data were divided into two groups. The cases included 50 patients (17 male and 33 female) with a mean age of 58.9 ±3.8 years and diagnosed with primary knee osteoarthritis of one or both knee joints. Controls included 50 persons (17 male and 33 female) with a mean age of 58.1 ±3.9 years without knee osteoarthritis and matched for age, sex, and body mass index. C-reactive protein qualitatively measured. Patients were radiologically assessed by Kellgren and Lawrence grading scale (grade 0-4). Results: C-reactive protein was positive in 41 out of 50 (82%) of knee osteoarthritis patients compared to 3 out of 50 (6%) of healthy controls (P = 0.001). C- reactive protein positivity among knee osteoarthritis patients were significantly associated with body mass index, positive family history of knee osteoarthritis, duration of diseases, and Kellgren and Lawrence grade (P <0.05). No significant association was found with sex, site of knee joint involvement, and knee pain severity (P >0.05). Conclusion: C-reactive protein positivity was significantly associated with knee osteoarthritis compared to healthy controls. Furthermore, body mass index, positive family history of knee osteoarthritis, early osteoarthritis, and Kellgren and Lawrence grade II, were significantly associated with positive C-reactive protein in knee osteoarthritis.